A new species of treefrog (Litoria) from Cape York Peninsula, Australia - Mcdonald, Keith R.; Rowley, Jodi J. L.; Richards, Stephen J.; Frankham, Greta J. (Zootaxa, 2016)
We describe a new species of treefrog from northern Australia. Litoria bella sp. nov. is morphologically and genetically most similar to frogs in the L. gracilenta and L. chloris groups but is distinguished from all members in these groups by a combination of a moderately large male body size (34.5–41.8 mm SVL), near-immaculate green dorsum, orange venter, bright orange digits and webbing, bluish purple lateral surfaces of the thighs, no pale canthal stripe, white bones, and a highly-pulsed, single-note, male advertisement call with a pulse rate of 56–64 pulses/s and dominant frequency of 2.6–2.8 kHz. Litoria bella sp. nov. has a patchy distribution across the Cape York Peninsula, inhabiting rainforest and monsoon vine thicket in close association with watercourses. The new species’ affinities lie with L. auae from southern New Guinea rather than with L. gracilenta from eastern Australia. Molecular data suggest that the L. gracilenta group should be expanded to include L. chloris and L. xanthomera, two moderately large green treefrogs from eastern Australia.